If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -16 + -3x = 26 Reorder the terms: -16 + 9x + -3x = 26 Combine like terms: 9x + -3x = 6x -16 + 6x = 26 Solving -16 + 6x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 6x = 26 + 16 Combine like terms: -16 + 16 = 0 0 + 6x = 26 + 16 6x = 26 + 16 Combine like terms: 26 + 16 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| y^2-5y-x+9=0 | | t^2=5r | | 5x-2x+x= | | 4(2x-3)=3+8-11 | | 4a+5(-2a-3)-a=-1 | | 2+3[4+3(11+3)+2]+5= | | .75x+18.50=.65+18.50 | | -6y+6=-2y(4y+6) | | x^2-1.62x-1=0 | | 25c-16=0 | | 20-42=5x+2+5x | | 15x-11=-41 | | 8z+9=8z-z | | 10-3c-7=-5 | | 5x-2+2x+6= | | 4(3+k)-7fork=0 | | 2-5(5v-8)=24-45v | | -3x+4x-3=-5 | | 384x+x=2494 | | 16r-4t-13t-17t= | | x^2+14x-68=4 | | 6y+5=4y+11 | | 5x^4567=5 | | 3=x^36 | | (-3i+4)*(3i+4)=25 | | (-3i+4)*(3i+4)= | | Z(z-12)=27 | | cx-ab=ax+d | | 1*(x-45)=x | | rx+rt=c | | 5x^2-20x=-11 | | 11x+7=6x+28 |